2015
DOI: 10.1111/ajgw.12148
|View full text |Cite
|
Sign up to set email alerts
|

Pre-flowering leaf removal alters grape microbial population and offers good potential for a more sustainable and cost-effective management of a Pinot Noir vineyard

Abstract: Background and Aims: The grapevine canopy microclimate, particularly temperature and relative humidity, is of crucial importance for predisposing grapes to lower or greater incidence of microbial infections. Because of global warming, the widely adopted leaf removal at veraison causes an increase in the temperature of the grape berry surface, leading to sunburn and deterioration of berry composition. Seeking a good alternative, a novel, preflowering leaf removal was studied and compared with post-flowering appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 44 publications
3
31
0
Order By: Relevance
“…As expected, the Shannon-Weaver diversity index revealed that, samples at the inside centre of the vineyard were richer than samples at the peripheral end of the vineyard. This could be explained by variability in temperature, humidity and UV-light within a block or vineyard, as highlighted in previous studies (Sternad Lemut et al 2015;Sui et al 2015). On another note, environmental conditions, such as solar radiation interfere with the production, germination and survival of conidia, which affect the life cycle of the pathogen.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…As expected, the Shannon-Weaver diversity index revealed that, samples at the inside centre of the vineyard were richer than samples at the peripheral end of the vineyard. This could be explained by variability in temperature, humidity and UV-light within a block or vineyard, as highlighted in previous studies (Sternad Lemut et al 2015;Sui et al 2015). On another note, environmental conditions, such as solar radiation interfere with the production, germination and survival of conidia, which affect the life cycle of the pathogen.…”
Section: Discussionmentioning
confidence: 80%
“…Sunlight exposure is generally high on vines at the peripheral end compared to the inside central vines due to canopy effect, this could result in a sterilizing effect on the bunch surfaces caused by UV radiation from sunlight, hence affecting the microbial composition and population. Previous researchers have also found that canopy microclimate conditions (air circulation, temperature and humidity) in grapevine (Sternad Lemut et al 2015) influence incidence of microbial infection in grapes. Furthermore, relative humidity in apples surfaces (Lahlali et al 2008) enhance the population of antagonistic yeasts.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Early defoliation decreases berry weight and thus grape yield itself [10,13], while defoliation during or after veraison affects primary and secondary synthesis of metabolites [19,20]. On the other hand, some reports have shown that early leaf removal is capable of improving the grape and wine quality [21,22]. Leaf removal before flowering decreased the grape yield of the Sangiovese variety, but on the other hand, it increased concentrations of anthocyanins and other phenolic compounds, due to changed microclimatic conditions in the zone of grape clusters [16].…”
Section: Introductionmentioning
confidence: 99%